A NOVEL CHARCTERIZATION METHOD ON MECHANICAL BEHAVIOR OF UNLOADING CURVES BY USING BEERKOVICH TIP - JIANG Rui; GAO Jun; MA Jin; LU ZeYuan; ZHU DeQuan (Jixie qiangdu)
Unloading curve analysis is a popular method in nan-indentation testing process,while the physical signification of the power-law exponent is obscure. Based on the Sneedon’s solution to elastic indentation of plane half infinite space,a new model was presented to characterize the plastic unloading behavior of Berkovich tip. The residual stress among elastic-plastic stain regions was taken into accounted. The plastic unloading behavior of Berkovich tip was characterized approximately using parabolic tip and conical tip. Experimental results indicated that parabolic tip can characterize the plastic unloading behavior more accurate and the rationality of the new model was validated.